Changes in Rhinovirus Protein 2C Allow Efficient Replication in Mouse Cells - Harris, Julie R. (American Society for Microbiology, 2003)
Rhinovirus type 16 was found to replicate in mouse L cells that express the viral receptor, human intercellular adhesion molecule 1 (ICAM-1). However, infection of these cells at a low multiplicity of infection leads to no discernible cytopathic effect, and low virus titers are produced. A variant virus, 16/L, was isolated after alternate passage of rhinovirus 16 between HeLa and ICAM-1 L cells. Infection of mouse cells with 16/L leads to higher virus titers, increased production of RNA, and total cytopathic effect. Three amino acid changes were identified in the P2 region of virus 16/L, and the adaptation phenotype mapped to two changes in protein 2C. The characterization of a rhinovirus host range mutant will facilitate the investigation of cellular proteins required for efficient viral growth and the development of a murine model for rhinovirus infection.